Modulatory effects of rutin on the expression of cytochrome P450s and antioxidant enzymes in human hepatoma cells - Karakurt Sedar (Acta Pharmaceutica)
Expression of a drug and xenobiotic metabolizing enzymes, cytochrome P450s (CYPs), and antioxidant enzymes can be modulated by various factors. The flavonoid rutin was investigated for its anti-carcinogen and protective effects as well as modulatory action on CYPs and phase II enzymes in human hepatocellular carcinoma cells. Rutin inhibited proliferation of HEPG2 cells in a dose-dependent manner with the IC50 value of 52.7 μmol L-1 and invasion of HEPG2 cells (21.6 %, p = 0.0018) and colony formation of those invaded cells (57.4 %, p < 0.0001). Rutin treatment also significantly increased early/late-stage apoptosis in HEPG2 cells (28.9 %, p < 0.001). Treatment by rutin significantly inhibited protein expressions of cytochrome P450-dependent CYP3A4 (75.3 %, p < 0.0001), elevated CYP1A1 enzymes (1.7-fold, p = 0.0084) and increased protein expressions of antioxidant and phase II reaction catalyzing enzymes, NQO1 (2.42-fold, p < 0.0001) and GSTP1 (2.03-fold, p < 0.0001). Besides, rutin treatment significantly inhibited mRNA expression of CYP3A4 (73.2 %, p=0.0014). Also, CYP1A1, NQO1 and GSTP1 mRNA expressions were significantly increased 2.77-fold (p = 0.029), 4.85- fold (p = 0.0051) and 9.84-fold (p < 0.0001), respectively.